An Analysis on Irony in Pride and Prejudice from the Perspective of Speech Act Theory - SUN, YAJIE (Pacific International Journal, 2022)
Pride and Prejudice, as Jane Austen’s most representative novel, has high literary value and research significance. The most notable feature of this novel is irony, which is employed to depict character images and highlight psychological activities and relationships among the characters. Irony is closely related to speech act theory, this article in the framework of speech act theory analyzes irony form the macro and micro perspective, thus proves the feasibility of application of theory of general linguistics to the analysis of fiction texts.